2016
DOI: 10.2169/internalmedicine.55.5578
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Link between Amyotrophic Lateral Sclerosis and Bullous Pemphigoid: Six New Cases and a Systematic Review of the Literature

Abstract: Objective Bullous pemphigoid in amyotrophic lateral sclerosis (BP-ALS) is rare and poorly understood. We herein assessed the association between ALS and BP using clinical and biological findings. Methods The clinical features of six new BP-ALS cases were described and collated with cases from a systematic literature review. Results Our six cases were combined with three other published cases. The mean disease duration (from ALS onset to the occurrence of BP) was 5.6±3.1 years. All patients had limb-onset ALS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Many studies noted that amyotrophic lateral sclerosis is associated with BP [2326]. Some studies have shown an association between multiple sclerosis and BP [27–30].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies noted that amyotrophic lateral sclerosis is associated with BP [2326]. Some studies have shown an association between multiple sclerosis and BP [27–30].…”
Section: Discussionmentioning
confidence: 99%
“…Riluzole (RZ) is the only available drug used for the treatment of amyotrophic lateral sclerosis (ALS) and diseases like Parkinson's disease, Huntington's disease and other mood ISSN 2056-9890 and anxiety disorders (Nakane et al, 2016). Even though riluzole is a most important pharmaceutical drug (Doble, 1996), no crystal structure of pure riluzole has been obtained to date, although several methods have been tried in the past (Mondal, Rao, et al, 2017;Mondal et al, 2018;Thomas et al, 2019;Yadav et al, 2018).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Subsequent characterization of these co-crystals in solution may result in concomitant modifications in the solubility and dissolution rates of this drug, and such studies are of extreme interest in the drug industry. This is the only available drug for the treatment of amyotrophic lateral sclerosis (ALS) and is also used to treat several diseases such as Parkinson’s disease, Huntington’s disease, and mood and anxiety disorders. Riluzole is a benzothiazole derivative (2-amino-6-(trifluoromethoxy)­benzothiazole) and consists of an amino group, a nitrogen atom on the ring, and an oxygen atom that are capable of forming strong hydrogen bonding interactions. However, the sulfur atom and the three fluorine atoms present in the molecule can act as hydrogen bond acceptors and can form weak intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%